Protective effects of apigenin in neurodegeneration: An update on the potential mechanisms - Ali Mohammadkhanizadeh; Mohammad Sheibani; Soroush Taherkhani; Davood Nourabadi; Seyed Mahdi Mohamadi-Zarch; Farnaz Nikbakht; Yaser Azizi (Brain Disorders)
Neurodegenerative diseases (NDs) are characterized by the progressive loss of neurons and neuronal connections, leading to cognitive decline, memory impairment, and motor dysfunction. Apigenin, a flavonoid found in various herbs and plants, has garnered significant attention for its neuroprotective properties. This review aims to provide an update on the potential mechanisms by which apigenin exerts its protective effects in neurodegeneration. Apigenin has been shown to possess potent antioxidant activity, which is thought to play a crucial role in its neuroprotective effects. Oxidative stress, resulting from an imbalance between the production of reactive oxygen species (ROS) and the body's antioxidant defenses, is a hallmark of neurodegenerative diseases. Apigenin has been demonstrated to scavenge ROS, thereby reducing oxidative stress and mitigating the damage to neurons. Inflammation is another key feature of neurodegenerative diseases, and apigenin has been found to possess anti-inflammatory properties. Apigenin has been shown to inhibit the production of pro-inflammatory cytokines, such as TNF-α and IL-1β, which are elevated in neurodegenerative diseases. Moreover, apigenin has been demonstrated to suppress the activation of microglia, the resident immune cells in the brain, which are thought to contribute to neuroinflammation. In addition, apigenin has been shown to activate the PI3K/Akt signaling pathway, which is involved in promoting neuronal survival and preventing apoptosis. In this review, we focus on the underlying mechanisms and signaling pathways involved in neurodegenerative disorders, as well as the diverse beneficial effects of apigenin within these pathways. The literature surveyed spans from 1980 to 2024. Also, systematic search was performed in Embase, MEDLINE, Scopus, Web of Science Core Collection, and Google Scholar for relevant references. Our findings highlight the potential mechanisms associated with the neuroprotective effects of apigenin.